Poly(A) binding KPAF4/5 complex stabilizes kinetoplast mRNAs in Trypanosoma brucei. Issue 15 (2nd July 2020) - Aphasizheva, Inna; Yu, Tian; Suematsu, Takuma; Liu, Qiushi; Mesitov, Mikhail V; Yu, Clinton; Huang, Lan; Zhang, Liye; Aphasizhev, Ruslan
Abstract: In Trypanosoma brucei, mitochondrial pre-mRNAs undergo 3′-5′ exonucleolytic processing, 3′ adenylation and uridylation, 5′ pyrophosphate removal, and, often, U-insertion/deletion editing. The 3′ modifications are modulated by pentatricopeptide repeat (PPR) Kinetoplast Polyadenylation Factors (KPAFs). We have shown that KPAF3 binding to the 3′ region stabilizes properly trimmed transcripts and stimulates their A-tailing by KPAP1 poly(A) polymerase. Conversely, poly(A) binding KPAF4 shields the nascent A-tail from uridylation and decay thereby protecting pre-mRNA upon KPAF3 displacement by editing. While editing concludes in the 5′ region, KPAF1/2 dimer induces A/U-tailing to activate translation. Remarkably, 5′ end recognition and pyrophosphate hydrolysis by the PPsome complex also contribute to mRNA stabilization. Here, we demonstrate that KPAF4 functions as a heterodimer with KPAF5, a protein lacking discernable motifs. We show that KPAF5 stabilizes KPAF4 to enable poly(A) tail recognition, which likely leads to mRNA stabilization during the editing process and impedes spontaneous translational activation of partially-edited transcripts. Thus, KPAF4/5 represents a poly(A) binding element of the mitochondrial polyadenylation complex. We present evidence that RNA editing substrate binding complex bridges the 5′ end-bound PPsome and 3′ end-bound polyadenylation complexes. This interaction may enable mRNA circularization, an apparently critical element of mitochondrial mRNA stability and quality control.